Pengaruh Sosial Media Marketing terhadap Keputusan Berkunjung ke Desa Wisata pada Gen Z di Jawa Barat melalui Travel Motivation - Shopy Anggraeni; Rahmat Priyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the influence of Social Media Marketing on the Visit Decision to tourism villages among Generation Z in West Java, with Travel Motivation as a mediating variable. The research is based on the rapid development of tourism villages and the dominance of Gen Z as active social media users who seek unique travel experiences. A quantitative method with a descriptive and verification approach was applied. Data were collected through questionnaires distributed to 100 Gen Z respondents from Bandung, Garut, and Sukabumi Regencies. The data analysis technique used path analysis and the Sobel test to examine the mediation effect. The results showed that Social Media Marketing has a positive and significant effect on both Travel Motivation and Visit Decision. Travel Motivation also significantly affects Visit Decision and mediates the relationship between Social Media Marketing and Visit Decision. Thus, social media-based marketing strategies are crucial in attracting Gen Z to visit tourism villages.